Neurorehabilitation of Traumatic Brain Injury (TBI): A Clinical Review - Michael Oberholzer; René M. Müri (Medical Sciences, 2019)
Traumatic brain injury (TBI) and its potential long-term consequences are of major concern for public health. Neurorehabilitation of affected individuals has some specific characteristics in contrast to neurorehabilitation of patients with acquired brain lesions of other aetiology. This review will deal with the clinical consequences of the distinct lesions of TBI. In severe TBI, clinical course often follows a typical initial sequence of coma; followed by disturbed consciousness; later, post-traumatic agitation and amnesia; and finally, recovery of function occurs. In the different phases of neurorehabilitation, physicians should be aware of typical medical complications such as paroxysmal sympathetic hyperactivity, posttraumatic hydrocephalus, and posttraumatic neuroendocrine dysfunctions. Furthermore, we address questions on timing and on existing evidence for different rehabilitation programmes and for holistic neuropsychological rehabilitation approaches.